Sulforaphane Treatment in Children with Autism: A Prospective Randomized Double-Blind Study - Magner, Martin; Thorová, Kateřina; Župová, Veronika; Houška, Milan; Švandová, Ivana; Novotná, Pavla; Tříska, Jan; Vrchotová, Naděžda; Soural, Ivo; Jílek, Ladislav (Nutrients, 2023)
Autism spectrum disorder (ASD) is a pervasive neurodevelopmental disorder with repetitive behaviour which affects interaction and communication. Sulforaphane (SFN), an isothiocyanate abundant in the seeds and sprouts of cruciferous vegetables, has been shown to be effective in alleviating autistic behaviour. We performed a prospective double-blind placebo-controlled study to examine the possible effect of SFN in a paediatric cohort aged three to seven years based on measurements of the Autism Diagnostic Observation Schedule-2 (ADOS-2), the Social Responsiveness Scale-2 (SRS-2), and the Aberrant Behaviour Checklist (ABC). The study consisted of three visits over the duration of 36 weeks (baseline, 18 weeks, and 36 weeks). Twenty-eight of the 40 randomized children completed the study. The mean total raw scores on ABC and SRS-2 improved in both groups, but none of the changes reached statistical significance (ABC: 0 weeks p = 0.2742, 18 weeks p = 0.4352, and 36 weeks 0.576; SRS-2: 0 weeks p = 0.5235, 18 weeks p = 0.9176, and 36 weeks 0.7435). Changes in the assessment of the ADOS-2 subscale scores also did not differ between the two study cohorts (ADOS-2: 0 weeks p = 0.8782, 18 weeks p = 0.4788, and 36 weeks 0.9414). We found no significant clinical improvement in the behavioural outcome measures evaluated in children with ASD aged 3-7 years that were treated with sulforaphane.
Keywords: Child; Autistic Disorder; lidé; dvojitá slepá metoda; Autism Spectrum Disorder; prospektivní studie; Double-Blind Method; dítě; isothiokyanatany; autistická porucha; Prospective Studies; Isothiocyanates; poruchy autistického spektra; Humans